The Effect of Handpaddle Aids on Freestyle Sprint Speed Over a Distance of 50 Meters - Kamila Asari; Nina Sutresna; Widi Kusumah (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study aims to determine the effect of handpaddle use on 50-meter freestyle sprint speed in female novice athletes from the PRI Aquarius Club Bandung. The background of this study is based on the importance of speed as a primary indicator of swimming performance, where arm muscle strength and stroke technique efficiency are determining factors. Handpaddles were chosen as a training medium because they provide additional resistance that can increase strength while improving stroke technique. The research method used an experiment with a one-group pretest-posttest design. The study sample consisted of 10 athletes selected by purposive sampling and divided into two groups: the experimental group with handpaddle training and the group without handpaddles. The research instrument was a 50-meter freestyle swimming speed test with a digital stopwatch. The results showed that the group training with handpaddles experienced a more significant increase in speed than the group without handpaddles. These findings indicate that handpaddles are effective as a training medium for increasing arm muscle strength, technique efficiency, and maintaining sprint speed until the final phase of the race. This study confirms the novelty of the 50-meter sprint distance focus and the benefits of handpaddles in maintaining performance in the critical phase of the race.